2021
DOI: 10.3389/fspor.2021.779824
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Joint Block Progression Training Improves Leaping Performance in Dancers

Abstract: The purpose of this study was to investigate the effect of a 12-week ankle-specific block progression training program on saut de chat leaping performance [leap height, peak power (PP), joint kinetics and kinematics], maximal voluntary isometric plantar flexion (MVIP) strength, and Achilles tendon (AT) stiffness. Dancers (training group n = 7, control group n = 7) performed MVIP at plantarflexed (10◦) and neutral ankle positions (0◦) followed by ramping isometric contractions equipped with ultrasound to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Dancers rely considerably on the ankle-joint complex for both saut de chat take-off propulsion and landing absorption. 12,23 Previous researchers have observed a propensity to shift load absorption proximally away from the ankle-joint in individuals with CAI. 24 One way this is achieved is by landing with greater dorsiflexion to employ a more “tightly packed” ankle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dancers rely considerably on the ankle-joint complex for both saut de chat take-off propulsion and landing absorption. 12,23 Previous researchers have observed a propensity to shift load absorption proximally away from the ankle-joint in individuals with CAI. 24 One way this is achieved is by landing with greater dorsiflexion to employ a more “tightly packed” ankle.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Strength in dancers has shown to both enhance performance and mitigate injury. [10][11][12] Huang et al 11 found that dancers who engaged in additional resistance exercise outside of dance training were 61% less likely to sustain an injury. Upon sustaining an ankle injury, and for that matter a repeated injury, it may be that the surrounding musculature is or becomes weaker.…”
Section: Introductionmentioning
confidence: 99%
“…Blanco and colleagues found large to very large associations between grand jeté leap height and CMJ and drop jump in ballet dancers with different skill levels, suggesting a relationship between ballet specific and non-specific jumps in this population 24 25 to improve ballet specific jumps. Moreover, recent findings suggest that supplementary training can have positive outcomes on ballet specific jumps 26 . As a consequence, performance in specific dance jumps that are vertically orientated and with an external rotation of the lower limbs, such as sauté, may be enhanced through training programs based on improving CMJ or SJ.…”
mentioning
confidence: 99%